Sistem Informasi Layanan Konsultasi Kesehatan Mental Berbasis Website - Faturizky, Bintang Ramadhana; Komalasari, Rita (Jurnal Teknologi Sistem Informasi, 2024)
Providing adequate accessibility to mental health services is a significant challenge in improving community well-being. The lack of accessibility to existing mental health services is a major problem that needs to be addressed. To overcome these problems, this research focuses on developing a web-based system using the waterfall method and utilizing Node.js and Express.js technologies. The developed system aims to increase the accessibility of mental health consultation services, allowing users to consult with professional doctors flexibly, wherever and whenever they need it. In the development of this system, special attention was paid to the scheduling and payment process. The system successfully implements features that allow users to easily schedule consultations with notifications sent after successful scheduling. In addition, the system also provides integrated payment facilities, so that users can easily pay consultation fees online. The system evaluation results show that the implementation of the waterfall method in the development of this web system provides satisfactory results, with key functions such as scheduling and payment running well. System users reported a positive experience in using this system, with accessibility and ease of use.